Critical Thinking for Global Citizenship Education: A Conceptual Framework - Golden, Brighid (Palgrave Studies in Global Citizenship Education and Democracy, 2025)
This open access book shares a two-part conceptual framework for critical global learning which weaves together theory and practice. The author shares the outcomes of her research and experiences developing students’ critical thinking skills within the context of global citizenship education. While rooted in literature and research findings, the book is personal and reflexive, as the author shares her experiences as a teacher trying, and sometimes failing, to support critical thinking development which allows readers to reflect on their own practice. The book will be of interest to academics working in higher education, initial teacher education, and global citizenship education.